(untitled) (City Dental College Journal, 2013)
Aims: The study was carried out among 1200 students of selected schools at Dhaka city to observe their attitude on oral hygiene through a pre-tested semi-structured questionnaire. Methods: The descriptive type of cross-sectional study was carried out among 1200 students of class IV-IX (aged 10-15 years) in the selected schools of Dhaka city from December 2011 to March 2012 to observe their attitude on oral hygiene through a pre-tested semi-structured questionnaire. Results: This study revealed that 92.5% of respondents understood the importance of taking care of oral cavity. Seventy seven percent (76.7%) of respondents agreed that regular brushing would prevent tooth decay. Of all, 69.2% respondents brushed their teeth regularly where, 69.2% brushed once a day, 27.5% brushed twice and only 3.3% brushed more than twice in a day. Ninety three percent (92.5%) used toothbrush and 83.3% used tooth paste for brushing their teeth. Among the respondents, 67.5% knew that sweet food caused harm to teeth and 50.0% thought that soft drinks would have the same effects on teeth. Sixty nine (69.2%) percent of respondents reported that they went to dentist on requirement basis and only 8.3% of respondents regularly went to dentist for checkup. An association was found between mothers occupation and regular brushing prevents tooth decay (p=0.04). Conclusion: The study suggested that the students would be the appropriate target group to receive the first organized intervention leading towards improving the oral health status and reducing prevalence of oral diseases through increasing their attitude. DOI: http://dx.doi.org/10.3329/cdcj.v10i2.16346 City Dent. Coll. J Voume-10, Number-2, July-2013